Tinjauan Historis Kecerdasan Buatan Dalam Games - Troy Troy (Journal of Animation and Games Studies, 2015)
Video games experienced rapid development in terms of gameplay, level of difficulty, and artificial intelligence. Artificial intelligence in computer games devoted to the ability to control the elements in the game that make intelligent decisions when a state has several options with different outcomes, resulting in behaviors that are relevant, effective, and useful. In the video game, scoring as well as compliance with the rules and visual display is presented by computers, not by humans. Computers also control the enemy character in the game, becoming another participant, acting as referee, as well as the condition of an area "game". This paper will discuss the development of artificial intelligence in video games in terms of gameplay, the level of difficulty and the development of video game device.Keywords: video games, artificial intelligence, history, gaming devices.AbstrakVideo game mengalami perkembangan yang pesat dari sisi gameplay, tingkat kesulitan, dan kecerdasan buatan. Kecerdasan buatan pada game dikhususkan pada kemampuan komputer mengendalikan unsur-unsur dalam game yang membuat keputusan cerdas ketika suatu kondisi memiliki beberapa pilihan dengan hasil akhir yang berbeda, sehingga menghasilkan perilaku yang relevan, efektif, dan berguna. Dalam video game, pemberian nilai serta kepatuhan terhadap aturan dan tampilan visual disajikan oleh komputer, bukan oleh manusia. Komputer juga yang melakukan kontrol karakter musuh dalam permainan, menjadi peserta lain, bertindak sebagai wasit, serta mengkondisikan suatu area “permainan”. Pada paper ini akan dibahas mengenai perkembangan kecerdasan buatan dalam video game dari sisi gameplay, tingkat kesulitan dan perkembangan perangkat video game.Kata kunci: video game, gameplay, kecerdasan buatan, sejarah, perangkat game.